The Relationship between Family Attitude and Family Caregiver Burden of Patients with Schizophrenia in Tangerang - Nurul Fitri; Karina Megasari Winahyu; Yudhia Frathidina (Universitas Muhammadiyah Tangerang, 2019)
Introduction: Schizophrenia is a mental disorder that occurs in the long term and affects the thought process which demanding for the required care. Negative attitudes can be one of the factors that influence the family burden that is getting heavier. This study aimed to determine the relationship of family attitudes to the family burden of caring for schizophrenic patients at the psychiatric hospital in Kota Tangerang. Methods: The study was a descriptive correlation with Cross-Sectional design. The population of this study was the family caregivers of patients with schizophrenia who visited the psychiatric clinic at Kota Tangerang Hospital. This study used the accidental sampling method, recruited as many as 64 people. The instrument of this study was the Burden Assessment Schedule (BAS) questionnaire and the Family Attitude Scale (FAS) had been examined the validity and reliability test. The Chi-square test was used for the statistical analysis to identify the relationship between family attitude and caregiver burden. Results: The results of this study were 23 respondents who had a positive attitude with a light burden of 52.2% while those with a negative attitude had 41 respondents with a heavy burden of 80.5. The p-value was 0.007 showed that there was a significant relationship between family attitudes and the burden of the family caring for patients with schizophrenia in psychiatric hospitals in Kota Tangerang Hospital. Conclusion: It suggests that health care providers need to consider the burden perceived by the caregivers so they are more likely to show a positive attitude in providing care for the beloved-one.Keywords: Caregiver Burden, Family Attitudes, Family Caregivers, Patients with Schizophrenia